KAJIAN PENGARUH SUHU UDARA INLET DAN KONSENTRASI MALTODEKSTRIN TERHADAP KUALITAS FISIK BUBUK JERUK NIPIS (Citrus aurantifolia) HASIL PENGERINGAN DENGAN SPRAY DRYER - , DEWI KUSUMANINGRUM, Dr. Joko Nugroho W.K., STP., M.Eng. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Drying of lime juice is an innovative processing of citrus fruit juice in an attempt to optimize of lime in Indonesia. Lime is a special product in spray drying process because limes have a low melting point and a low solids content was 8 % so in spray drying needed maltodekstrin as a carrier agent. This research aims to determine the effect of inlet temperature and maltodekstrin concentration on the physical quality of lime powder and performance of spray dryer. Drying process using a pilot-scale spray dryer with a chamber that have diameter 60 cm and high of chamber 160 cm that have capasity 1-4 kg/hour. Atomizer uses a pneumatic nozzle type. Product that will dried was a mixture of 600 gram lemon juice with maltodekstrin. Experimental design using two factors was variation maltodekstrin concentration (maltodekstrin solids/ lime juice solids) of 15% , 25% , 35% and spray dried at inlet air temperatures of 190, 200, and 210oC. The feed flow rate was set by pressure of 2 bar in compressor and debit of air is used 0,034 m3/s. The results showed that the inlet air temperature and maltodekstrin concentration significant affect on the quality of lime powder and performance of spray dryer. The increase in inlet air temperature and maltodekstrin concentration maked the moisture content will decreases but solubility, degree of whiteness, yield and efficiency production will increases. The resulting particle size classified as fine (65% passes 100 mesh). The combination of inlet air temperature of 210oC and 35% maltodekstrin concentration produces lime powder with the best quality. Keywords: Spray dryer , lime powder , concentration , inlet air temperature